Exploring death - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
This program features three scholars who share their insights about new ways of looking at and making peace with death. We'll explore the inner workings of the immune system and the death of the body, we'll also look at the death of the brain and the promise of artificial intelligence and finally we'll explore cosmic death and human hope.
Executive producer, Nasuhi yurt
Host : MaryLynn Schiavi
DVD format
Keywords: Death -- Psychological aspects; Death